Composite electrode coating with reversible protection function and preparation method and application thereof
By using a composite electrode coating prepared with a specific polymer matrix and conductive agent, the problem of thermal runaway in lithium-ion batteries and lack of reversible functions in existing PTC electrodes is solved, and efficient thermal safety protection and multiple reversibility of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202510079134.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The thermal runaway problem of existing lithium-ion batteries leads to insufficient safety, and existing thermal protection technologies such as PTC electrodes lack reversible functions and cannot be applied on a large scale.
A composite electrode coating with reversible protection function was prepared using a specific polymer matrix (polymer A with a melting index less than 0.5 g/10 min and polymer B with a melting point of 70~170 ℃) and a specific conductive agent (an aspect ratio of 2~10000). The coating has a low resistivity at room temperature, a suitable resistance to change temperature, and a high lift-resistance ratio. It can quickly turn off the electrochemical reaction at high temperatures and prevent thermal runaway.
The thermal safety protection of lithium-ion batteries is achieved, the safety performance of the battery is improved, and the reversibility of the composite electrode coating allows it to restore electrochemical activity in temperature changes multiple times.
Smart Images

Figure CN119852564A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary battery composite electrodes, and in particular to a composite electrode coating with a reversible protection function and a preparation method and application thereof. Background Art
[0002] Although lithium-ion batteries have been widely used in electric vehicles, energy storage power stations and mobile electronic devices, safety issues are still an important technical bottleneck restricting the large-scale application of lithium-ion batteries. Among them, thermal runaway is one of the main reasons for the unsafe behavior of lithium-ion batteries.
[0003] Establishing self-excited thermal protection technology inside the battery is an effective way to suppress thermal runaway of the battery. Currently developed technologies such as positive temperature coefficient (PTC) electrodes, thermal shutdown diaphragms, and thermal polymerization additives can achieve certain thermal protection, but none of them have reversible protection functions. Technologies such as PTC electrodes, thermal shutdown diaphragms, and thermal polymerization additives that do not have reversible protection functions are incompatible with production processes and cannot be applied on a large scale; moreover, all performance is sacrificed for only one protection, increasing the cost of use. From the analysis of the working mechanism, technologies such as thermal shutdown diaphragms and thermal polymerization additives cannot achieve reversible protection functions. From an application perspective, it is more advantageous to develop PTC electrodes with reversible protection functions.
[0004] The main reason why the polymer substrate / conductive filler type PTC electrode does not have a reversible function is that there is a lack of interaction between the polymer substrate and the conductive filler, which causes the conductive filler to be unable to re-form a good conductive network as the volume of the polymer substrate shrinks. Therefore, the present invention develops a composite electrode coating with low room temperature resistivity, high lift-to-resistance ratio, and reversible protection function for thermal safety protection of lithium-ion batteries. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a composite electrode coating with reversible protection function and a preparation method and application thereof. The composite electrode coating has low room temperature resistivity, appropriate resistance change temperature, high rise-to-resistance ratio, and many reversible thermal response times, and is very suitable for thermal safety protection of lithium-ion batteries.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] In a first aspect, the present invention provides a composite electrode coating with a reversible protection function, wherein a polymer matrix and a conductive agent are uniformly mixed to obtain a composite electrode coating with a reversible protection function;
[0008] The polymer matrix includes a polymer A and a polymer B; wherein the melt index of the polymer A is less than 0.5 g / 10 min, and the melting point of the polymer B is 70-170°C;
[0009] The conductive agent has an aspect ratio of 2 to 10,000.
[0010] In view of the problem that the self-excited thermal protection technology in the prior art does not have a reversible protection function, the present invention adopts a specific polymer matrix (polymer A with a melt index less than 0.5 g / 10 min and polymer B with a melting point of 70~170°C) and a specific conductive agent (aspect ratio of 2~10000) to prepare a composite electrode coating with a reversible protection function. The composite electrode coating exhibits a large lift-to-drag ratio and can quickly achieve thermal safety protection for the battery. In the composite electrode coating of the present invention, a specific conductive agent can be uniformly dispersed in a specific polymer matrix. When the temperature is lower than the transition temperature (below 60°C), the conductive agents contact each other to form a conductive network with low resistivity, which can be regarded as a conductor, and the electrochemical reaction of the composite electrode proceeds normally; when the temperature is higher than the transition temperature (higher than 120°C), the polymer matrix expands within a certain range, causing the conductive agent to temporarily move, the spacing between the conductive agents increases, the conductive network is destroyed, the resistivity of the coating rises sharply, and it can be regarded as an insulator. The composite electrode loses its electrochemical activity, thereby inhibiting the occurrence of thermal runaway; and when the temperature drops from high temperature back to below the transition temperature, the polymer matrix shrinks, and thanks to the interaction between the polymer substrate and the conductive agent, the conductive network is reconstructed, the resistivity of the coating returns to its initial low level, and it becomes a conductor again, and the electrochemical performance of the composite electrode can be restored to its initial state.
[0011] Furthermore, the mass ratio of the polymer A to the polymer B is 1:99-50:50.
[0012] Furthermore, the polymer A includes but is not limited to at least one of block copolymer polypropylene, random copolymer polypropylene, ultra-high molecular weight polyethylene, cross-linked polyethylene, and polyvinyl chloride; the polymer B includes but is not limited to at least one of polymethyl methacrylate, thermoplastic polyurethane rubber, low molecular weight polyethylene, polyethylene oxide, medium density polyethylene, polymethacrylic acid, polypropylene, and polyvinyl alcohol.
[0013] Furthermore, the conductive agent includes but is not limited to at least one of short rod-shaped carbon fibers, nickel-plated carbon fibers, nanocarbon fibers, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene nanosheets, mesophase carbon microspheres, nano-nickel particles, nano-silver particles, silver sulfide powder, and tin powder.
[0014] Furthermore, the lift-to-drag ratio of the PTC effect of the composite electrode coating is greater than or equal to 3.
[0015] Furthermore, the mass of the polymer matrix is 65% to 99% of the total mass of the composite electrode coating.
[0016] Furthermore, the mass of the polymer matrix is 80% to 97.5% of the total mass of the composite electrode coating.
[0017] Furthermore, the mass of the conductive agent is 1% to 35% of the total mass of the composite electrode coating.
[0018] Furthermore, the mass of the conductive agent is 2.5% to 20% of the total mass of the composite electrode coating.
[0019] Furthermore, the composite electrode coating has a PTC effect in a direction perpendicular to the electrode plane.
[0020] Furthermore, the reversible thermal response times of the composite electrode coating is greater than or equal to 2 times.
[0021] Furthermore, the reversible thermal response times of the composite electrode coating is greater than or equal to 5 times.
[0022] Furthermore, the PTC effect resistance temperature of the composite electrode coating is 60°C to 120°C. Generally, the PTC effect resistance temperature of the composite electrode coating is close to the melting point of the polymer matrix. The present invention selects one or more of block copolymer polypropylene, random copolymer polypropylene, ultra-high molecular weight polyethylene, cross-linked polyethylene, and polyvinyl chloride with a melting index of less than 0.5 g / 10 min, and one or more of polymethyl methacrylate, thermoplastic polyurethane rubber, low molecular weight polyethylene, polyethylene oxide, medium density polyethylene, polymethacrylic acid, polypropylene, and polyvinyl alcohol with a melting point of 70 to 170°C, and the two are matched in a specific ratio as a polymer matrix, so that the resistance temperature can be controlled within the range of 60°C to 120°C.
[0023] Furthermore, the PTC effect resistance temperature of the composite electrode coating is 80°C to 110°C.
[0024] In a second aspect, the present invention provides application of the composite electrode coating with reversible protection function in a composite electrode of a lithium-ion battery.
[0025] In a third aspect, the present invention provides a lithium-ion battery composite electrode, comprising the composite electrode coating with reversible protection function, a current collector and an active material layer.
[0026] Furthermore, the thickness of the composite electrode coating accounts for 0.1% to 20% of the total thickness of the composite electrode.
[0027] Furthermore, the thickness of the composite electrode coating accounts for 0.1% to 10% of the total thickness of the composite electrode.
[0028] Furthermore, the current collector is aluminum foil or copper foil, that is, a conventional positive electrode or negative electrode current collector of a lithium-ion battery.
[0029] Furthermore, the active material layer includes the following components in percentage by mass: 90-97% active material, 0.5-5% binder, and 0.5-5% conductive carbon.
[0030] Furthermore, the active material is lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMnO2), lithium nickel cobalt aluminum ternary composite material (LiNi 1-x-y Co x Al y O2), lithium nickel manganese cobalt ternary composite materials (LiNi x Mn y Co z O2), graphite, MCMB, that is, the conventional positive or negative electrode material of lithium-ion batteries.
[0031] In a fourth aspect, the present invention provides a method for preparing the lithium ion battery composite electrode, comprising the following steps:
[0032] S1: blending the conductive agent and the polymer matrix by a solution method or a melt method to obtain a polymer matrix / conductive agent composite;
[0033] S2: uniformly coating the polymer matrix / conductive agent composite on the current collector by solution coating or hot pressing, and obtaining the current collector-coating composite after drying;
[0034] S3: coating a layer of active material slurry on the current collector-coating composite, and obtaining a lithium-ion battery composite electrode after drying.
[0035] Furthermore, when the blending and mixing is performed by the melt method, the mixture is heated to a temperature 10° C. to 50° C. above the melting point of the polymer matrix.
[0036] Furthermore, when the solution method is used for blending, stirring is used to uniformly mix the polymer matrix and the conductive agent.
[0037] Furthermore, when the solution method is used for blending and mixing, the polymer matrix / conductive agent composite is coated on the current collector by a solution coating method; when the melt method is used for blending and mixing, the polymer matrix / conductive agent composite is hot pressed onto the current collector by a hot pressing method.
[0038] Compared with the prior art, the present invention is beneficial in that:
[0039] (1) The composite electrode coating provided by the present invention has low resistivity at room temperature, suitable resistance transition temperature, high lift-to-resistance ratio, and a large number of reversible thermal responses. It can shut down the electrochemical reaction of the lithium-ion battery at a set temperature, prevent thermal runaway, and improve the safety performance of the lithium-ion battery.
[0040] (2) The lithium-ion battery composite electrode based on the composite electrode coating has the advantages of stable characteristics and good electrochemical performance at room temperature. At the same time, the lithium-ion battery composite electrode is highly compatible with the production process of conventional lithium-ion batteries and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 , Figure 2 All of them are schematic diagrams of the composite electrode coating structure with reversible protection function of the present invention. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In a first aspect, the present invention provides a composite electrode coating with a reversible protection function, wherein a polymer matrix and a conductive agent are uniformly mixed to obtain a composite electrode coating with a reversible protection function;
[0044] The polymer matrix includes a polymer A and a polymer B; wherein the melt index of the polymer A is less than 0.5 g / 10 min, and the melting point of the polymer B is 70-170°C;
[0045] The conductive agent has an aspect ratio of 2 to 10,000.
[0046] In some examples, the mass ratio of the polymer A to the polymer B is 1:99 to 50:50.
[0047] In some examples, the polymer A includes but is not limited to at least one of block copolymer polypropylene, random copolymer polypropylene, ultra-high molecular weight polyethylene, cross-linked polyethylene, and polyvinyl chloride; the polymer B includes but is not limited to at least one of polymethyl methacrylate, thermoplastic polyurethane rubber, low molecular weight polyethylene, polyethylene oxide, medium density polyethylene, polymethacrylic acid, polypropylene, and polyvinyl alcohol.
[0048] In some examples, the conductive agent includes but is not limited to at least one of short rod-shaped carbon fibers, nickel-plated carbon fibers, nanocarbon fibers, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene nanosheets, mesophase carbon microspheres, nano-nickel particles, nano-silver particles, silver sulfide powder, and tin powder.
[0049] In some examples, the lift-to-drag ratio of the PTC effect of the composite electrode coating is greater than or equal to 3.
[0050] In some examples, the mass of the polymer matrix is 65% to 99% of the total mass of the composite electrode coating.
[0051] In some examples, the mass of the conductive agent is 1% to 35% of the total mass of the composite electrode coating.
[0052] In some examples, the PTC effect resistance temperature of the composite electrode coating is 60°C to 120°C.
[0053] In a second aspect, the present invention provides application of the composite electrode coating with reversible protection function in a composite electrode of a lithium-ion battery.
[0054] In a third aspect, the present invention provides a lithium-ion battery composite electrode, comprising the composite electrode coating with reversible protection function, a current collector and an active material layer.
[0055] In some examples, the thickness of the composite electrode coating is 0.1% to 20% of the total thickness of the composite electrode.
[0056] In some examples, the current collector is aluminum foil or copper foil, that is, a conventional positive or negative electrode current collector of a lithium-ion battery.
[0057] In some examples, the active material layer includes the following components in percentage by mass: 90-97% active material, 0.5-5% binder, and 0.5-5% conductive carbon.
[0058] In some examples, the active material is lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMnO2), lithium nickel cobalt aluminum ternary composite material (LiNi 1-x-y Co x Al y O2), lithium nickel manganese cobalt ternary composite materials (LiNi x Mn y Co z O2), graphite, MCMB, that is, the conventional positive or negative electrode material of lithium-ion batteries.
[0059] The method for preparing the lithium ion battery composite electrode comprises the following steps:
[0060] S1: blending the conductive agent and the polymer matrix by a solution method or a melt method to obtain a polymer matrix / conductive agent composite;
[0061] S2: uniformly coating the polymer matrix / conductive agent composite on the current collector by solution coating or hot pressing, and obtaining the current collector-coating composite after drying;
[0062] S3: coating a layer of active material slurry on the current collector-coating composite, and obtaining a lithium-ion battery composite electrode after drying.
[0063] Example 1
[0064] A lithium-ion battery composite electrode (positive electrode)
[0065] (1) Preparation of polymer matrix / conductive agent composite:
[0066] By mass fraction, 48.5% polyvinyl chloride (melt index of 0.3 g / 10 min), 48.5% polymethyl methacrylate (melting point of 125 °C), and 3% multi-walled carbon nanotubes (aspect ratio of 2000) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0067] (2) Preparation of positive electrode:
[0068] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0069] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0070] Example 2
[0071] A lithium-ion battery composite electrode (positive electrode)
[0072] (1) Preparation of polymer matrix / conductive agent composite:
[0073] By mass fraction, 24% ultra-high molecular weight polyethylene (melt index of 0.01 g / 10 min), 56% medium density polyethylene (melting point of 126 °C), and 20% graphene nanosheets (aspect ratio of 1200) were added to xylene and mixed, and heated to 130 °C for stirring to obtain a uniformly dispersed slurry.
[0074] (2) Preparation of positive electrode:
[0075] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0076] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0077] Example 3
[0078] A lithium-ion battery composite electrode (positive electrode)
[0079] (1) Preparation of polymer matrix / conductive agent composite:
[0080] By mass fraction, 24% polyvinyl chloride (melt index of 0.3 g / 10 min), 56% polypropylene (melting point of 162 ℃), and 20% single-walled carbon nanotubes (aspect ratio of 1500) were added into an internal mixer, and the parameters were set to 180 ℃ and 100 rpm. After the internal mixer was mixed evenly, granulation was carried out. The obtained polymer matrix / conductive agent composite particles were hot pressed, and the parameters were set to 180 ℃ and 20 Mpa to obtain a uniform polymer matrix / conductive agent composite film with a thickness of 15 μm.
[0081] (2) Preparation of positive electrode:
[0082] The polymer matrix / conductive agent composite film prepared in step (1) was hot pressed onto the front and back sides of the 16 μm positive electrode current collector Al foil by hot pressing. The hot pressing parameters were set to 180 °C and 2.5 MPa to obtain a current collector-coating composite, wherein the coating thickness was 15 μm.
[0083] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF are added to the solvent N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry is evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode is cold pressed, trimmed, cut, stripped, and the positive electrode ears are welded to obtain the positive electrode sheet.
[0084] Example 4
[0085] A lithium-ion battery composite electrode (positive electrode)
[0086] (1) Preparation of polymer matrix / conductive agent composite:
[0087] By mass fraction, 48.5% polyvinyl chloride (melt index of 0.3 g / 10 min), 48.5% polymethacrylic acid (melting point of 125 °C), and 3% multi-walled carbon nanotubes (aspect ratio of 2000) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0088] (2) Preparation of positive electrode:
[0089] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0090] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0091] Example 5
[0092] A lithium-ion battery composite electrode (positive electrode)
[0093] (1) Preparation of polymer matrix / conductive agent composite:
[0094] By mass fraction, 42% polyvinyl chloride (melt index of 0.3 g / 10 min), 42% polymethyl methacrylate (melting point of 125 °C), and 18% short rod-shaped carbon fiber (aspect ratio of 10) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0095] (2) Preparation of positive electrode:
[0096] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0097] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0098] Example 6
[0099] A lithium-ion battery composite electrode (positive electrode)
[0100] (1) Preparation of polymer matrix / conductive agent composite:
[0101] By mass fraction, 42% ultra-high molecular weight polyethylene (melt index of 0.01 g / 10 min), 42% medium density polyethylene (melting point of 126 °C), and 18% short rod-shaped carbon fiber (aspect ratio of 10) were added to xylene and mixed, and heated to 130 °C for stirring to obtain a uniformly dispersed slurry.
[0102] (2) Preparation of positive electrode:
[0103] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0104] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0105] Example 7
[0106] A lithium-ion battery composite electrode (positive electrode)
[0107] (1) Preparation of polymer matrix / conductive agent composite:
[0108] By mass fraction, 24% ultra-high molecular weight polyethylene (melt index of 0.01 g / 10 min), 56% medium density polyethylene (melting point of 126 °C), and 20% nano carbon fiber (aspect ratio of 500) were added to xylene and mixed, and heated to 130 °C for stirring to obtain a uniformly dispersed slurry.
[0109] (2) Preparation of positive electrode:
[0110] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0111] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0112] Example 8
[0113] A lithium-ion battery composite electrode (positive electrode)
[0114] (1) Preparation of polymer matrix / conductive agent composite:
[0115] By mass fraction, 24% ultra-high molecular weight polyethylene (melt index of 0.01 g / 10 min), 56% medium density polyethylene (melting point of 126 °C), and 20% mesophase carbon microspheres (aspect ratio of 2) were added to xylene and mixed, and heated to 130 °C for stirring to obtain a uniformly dispersed slurry.
[0116] (2) Preparation of positive electrode:
[0117] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0118] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0119] Example 9
[0120] A lithium-ion battery composite electrode (positive electrode)
[0121] (1) Preparation of polymer matrix / conductive agent composite:
[0122] By mass fraction, 24% ultra-high molecular weight polyethylene (melt index of 0.01 g / 10 min), 56% thermoplastic polyurethane rubber (melting point of 80 °C), and 20% short rod-shaped carbon fiber (aspect ratio of 10) were added to xylene and mixed, and heated to 130 °C for stirring to obtain a uniformly dispersed slurry.
[0123] (2) Preparation of positive electrode:
[0124] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0125] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0126] Example 10
[0127] A lithium-ion battery composite electrode (positive electrode)
[0128] (1) Preparation of polymer matrix / conductive agent composite:
[0129] By mass fraction, 24% ultra-high molecular weight polyethylene (melt index of 0.01 g / 10 min), 56% low molecular weight polyethylene (melting point of 113 °C), and 20% short rod-shaped carbon fiber (aspect ratio of 10) were added to xylene and mixed, and heated to 130 °C for stirring to obtain a uniformly dispersed slurry.
[0130] (2) Preparation of positive electrode:
[0131] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0132] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0133] Embodiment 11
[0134] A lithium-ion battery composite electrode (negative electrode)
[0135] (1) Preparation of polymer matrix / conductive agent composite:
[0136] By mass fraction, 48.5% polyvinyl chloride (melting index of 0.3 g / 10 min), 48.5% polymethyl methacrylate (melting point of 125 °C), and 3% multi-walled carbon nanotubes (aspect ratio of 2000) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0137] (2) Preparation of negative electrode sheet:
[0138] The slurry prepared in step (1) was uniformly coated on the front and back sides of a negative electrode current collector Cu foil with a thickness of 12 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0139] By mass fraction, 97.7% of negative electrode active material graphite, 1.3% of thickener CMC, and 1.0% of binder SBR were added to solvent deionized water and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was applied to the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the negative electrode ears were welded to obtain the negative electrode sheet.
[0140] Comparative Example 1
[0141] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and a uniformly dispersed black slurry was obtained after planetary ball milling. The black slurry was evenly coated on the front and back sides of the positive electrode current collector Al foil with a thickness of 16 μm by roller coating. After drying, the above-mentioned pole piece was cold pressed, trimmed, cut, stripped, and the positive electrode ear was welded to obtain the positive electrode sheet.
[0142] Comparative Example 2
[0143] (1) By mass fraction, 97% polymethyl methacrylate (melting point: 125 °C) and 3% multi-walled carbon nanotubes (aspect ratio: 2000) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0144] (2) Preparation of positive electrode:
[0145] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0146] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0147] Comparative Example 3
[0148] (1) By mass fraction, 97% polyvinyl chloride (melt index of 0.3 g / 10 min) and 3% multi-walled carbon nanotubes (aspect ratio of 2000) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0149] (2) Preparation of positive electrode:
[0150] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0151] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0152] Comparative Example 4
[0153] (1) Preparation of polymer matrix / conductive agent composite:
[0154] By mass fraction, 48.5% polyvinyl chloride (melting index of 0.3 g / 10 min), 48.5% polymethyl methacrylate (melting point of 125 °C), and 3% mesocarbon microspheres (aspect ratio of 1) were added to N,N-dimethylformamide (DMF) and mixed to obtain a uniformly dispersed slurry.
[0155] (2) Preparation of positive electrode:
[0156] The slurry prepared in step (1) was uniformly coated on the front and back sides of a positive electrode current collector Al foil with a thickness of 16 μm by a solution coating method, and a current collector-coating composite was obtained after drying, wherein the thickness of the coating was 10 μm.
[0157] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to N-methylpyrrolidone (NMP) and mixed, and then subjected to planetary ball milling to obtain a uniformly dispersed black slurry. The black slurry was evenly coated on the above-mentioned current collector-coating composite by roller coating, and after drying, the above-mentioned electrode was cold pressed, trimmed, cut, stripped, and the positive electrode ears were welded to obtain the positive electrode sheet.
[0158] Assembling lithium-ion secondary batteries
[0159] The positive electrode sheets prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were assembled into lithium-ion secondary batteries according to the following method:
[0160] According to the mass fraction, 97.7% of negative electrode active material graphite, 1.3% of thickener CMC, and 1.0% of binder SBR were added to the solvent deionized water and mixed, and a uniformly dispersed black slurry was obtained after planetary ball milling. The black slurry was applied to the front and back sides of the negative electrode current collector Cu foil with a thickness of 12 μm by roller coating. After drying, the above-mentioned pole piece was cold pressed, trimmed, cut, stripped, and welded to the negative electrode ear to obtain the negative electrode sheet.
[0161] 1.15M LiPF6 was dissolved in a mixed solution of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and fluorobenzene (the volume ratio of each component was 30:30:35:5) as the electrolyte.
[0162] Using polyethylene as a separator, the positive electrode sheets prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were respectively assembled with the above-mentioned negative electrode sheets and electrolyte to form lithium-ion secondary batteries. The battery size was 50 mm (length) × 42 mm (width) × 34 mm (height), and the rated capacity of the battery was 3410 mAh.
[0163] The negative electrode sheet prepared in Example 11 was assembled into a lithium ion secondary battery according to the following steps:
[0164] By mass fraction, 97% of the positive electrode active material LiCoO2, 1.5% of the conductive agent Super-P, and 1.5% of the binder PVDF were added to the solvent N-methylpyrrolidone (NMP) and mixed, and a uniformly dispersed black slurry was obtained after planetary ball milling. The black slurry was evenly coated on the front and back sides of the positive electrode current collector Al foil with a thickness of 16 μm by roller coating. After drying, the above-mentioned pole piece was cold pressed, trimmed, cut, stripped, and the positive electrode ear was welded to obtain the positive electrode sheet.
[0165] 1.15M LiPF6 was dissolved in a mixed solution of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and fluorobenzene (the volume ratio of each component was 30:30:35:5) as the electrolyte.
[0166] Using polyethylene as a separator, the negative electrode sheet prepared in Example 11, the positive electrode sheet and the electrolyte were assembled into a lithium-ion secondary battery with a battery size of 50 mm (length) × 42 mm (width) × 34 mm (height) and a rated capacity of 3410 mAh.
[0167] Performance Testing
[0168] 1. Lithium-ion secondary battery performance test
[0169] (1) Nail penetration safety performance test of lithium-ion secondary batteries
[0170] In the nail penetration test, the nail diameter D = 3 mm and the penetration speed V = 80 mm / s
[0171] The pass rate of lithium-ion secondary batteries was calculated based on the criteria of no fire, no combustion, and no explosion. The test results are shown in Table 1.
[0172] (2) Thermal shock safety performance test of lithium-ion secondary batteries
[0173] In the thermal shock test, the battery was charged to 4.4 V at a constant current of 0.5C at 25°C, and then charged to 0.05 C at a constant voltage of 4.4 V. The battery was then placed in a constant temperature box, the temperature of the constant temperature box was increased to 150°C at a heating rate of 5°C / min, and kept at 150°C for 1 hour.
[0174] The pass rate of lithium-ion secondary batteries was calculated based on the criteria of no fire, no combustion, and no explosion. The test results are shown in Table 1.
[0175] (3) Thermal response protection reversibility test of lithium-ion secondary batteries
[0176] In the thermal response protection reversibility test, at 25°C, the battery was charged to 4.4 V at a constant current of 0.5C, and then charged to 0.05 C at a constant voltage of 4.4 V. The battery was then placed in a constant temperature box, and the temperature was raised to 120°C at a heating rate of 5°C / min and kept at 120°C for 1 hour. The battery that did not catch fire, burn or explode was taken out and restored to 25°C, and the battery was discharged to 3.0 V at a constant current of 0.5C.
[0177] The pass rate of lithium-ion secondary batteries was calculated based on the criterion that the constant current discharge capacity reached 80% or more of the charge capacity. The test results are shown in Table 1.
[0178] Table 1: Performance test results of lithium-ion secondary batteries
[0179]
[0180] The data of Example 1 and Example 11 in Table 1 show that the composite electrode coating with reversible protection function of the present invention can improve the safety performance of lithium-ion batteries regardless of whether it is applied to the composite positive electrode of a lithium-ion battery or the composite negative electrode of a lithium-ion battery, but the reversibility on the negative electrode side is slightly worse than that on the positive electrode side, which may be related to the destruction of the SEI layer on the negative electrode surface at high temperature.
[0181] The data of Example 1, Example 4, Example 5 and Example 6 in Table 1 show that by selecting different polymers, the resistance change temperature of the composite electrode coating with reversible protection function and the reversibility of the PTC effect can be adjusted, so that the safety performance of the lithium-ion secondary battery is improved.
[0182] The data of Example 2, Example 7, Example 8 and Comparative Example 4 in Table 1 show that by selecting conductive carbon with a larger aspect ratio, the lift-to-drag ratio of the polymer matrix / conductive agent composite electrode coating can be improved, making the thermal shutdown performance of the lithium-ion battery composite electrode more reliable, thereby improving the safety of the lithium-ion secondary battery.
[0183] From the data of Example 3, Example 9, and Example 10 in Table 1, it can be seen that by replacing polypropylene with thermoplastic polyurethane rubber or low molecular weight polyethylene with a lower melting point, the resistance switching temperature of the polymer matrix / conductive agent composite electrode coating is within the range of 80°C to 110°C, and the electrode reaction can be shut down before the onset of thermal runaway, thereby improving the safety of the lithium-ion secondary battery.
[0184] The common lithium-ion secondary battery in Comparative Example 1 does not contain a polymer matrix / conductive agent composite electrode coating and has the worst safety performance.
[0185] The polymer matrix of the composite electrode coating in Comparative Example 2 only uses a Class B polymer with a melting point of 70-170° C., which has a thermal protection effect and good safety performance, but is not reversible.
[0186] The polymer matrix of the composite electrode coating in Comparative Example 3 only uses a Class A polymer with a melt index of less than 0.5 g / 10min. Since this type of polymer hardly expands near the melting point, the PTC strength of the material is low, thermal shutdown cannot be achieved, the safety performance is poor, and it is not reversible.
[0187] In summary, the present invention uses a polymer A with a melt index of less than 0.5 g / 10 min and a polymer B with a melting point of 70-170 ° C as a polymer matrix, and a conductive agent with an aspect ratio of 2-10000 to prepare a composite electrode coating with a reversible protection function. The composite electrode coating has a low resistivity at room temperature, a suitable resistance change temperature, and a large lift-to-resistance ratio. It can quickly shut down the electrochemical reaction of the lithium-ion battery at high temperature, prevent thermal runaway, and improve the safety performance of the lithium-ion battery. The lithium-ion battery composite electrode based on the composite electrode coating has the advantages of stable characteristics and good electrochemical performance at room temperature. At the same time, the lithium-ion battery composite electrode is highly compatible with the production process of conventional lithium-ion batteries and has good application prospects.
[0188] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A composite electrode coating with reversible protection function, characterized in that: The polymer matrix and the conductive agent are uniformly mixed to obtain a composite electrode coating with a reversible protection function; The polymer matrix includes a polymer A and a polymer B; wherein the melt index of the polymer A is less than 0.5 g / 10 min, and the melting point of the polymer B is 70-170°C; The conductive agent has an aspect ratio of 2 to 10,000.
2. The composite electrode coating with reversible protection function according to claim 1, characterized in that: The polymer A includes but is not limited to at least one of block copolymer polypropylene, random copolymer polypropylene, ultra-high molecular weight polyethylene, cross-linked polyethylene, and polyvinyl chloride; the polymer B includes but is not limited to at least one of polymethyl methacrylate, thermoplastic polyurethane rubber, low molecular weight polyethylene, polyethylene oxide, medium density polyethylene, polymethacrylic acid, polypropylene, and polyvinyl alcohol.
3. The composite electrode coating with reversible protection function according to claim 1, characterized in that: The conductive agent includes but is not limited to at least one of short rod-shaped carbon fibers, nickel-plated carbon fibers, nanocarbon fibers, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene nanosheets, mesophase carbon microspheres, nano-nickel particles, nano-silver particles, silver sulfide powder, and tin powder.
4. The composite electrode coating with reversible protection function according to claim 1, characterized in that: The mass of the polymer matrix is 65% to 99% of the total mass of the composite electrode coating; the mass of the conductive agent is 1% to 35% of the total mass of the composite electrode coating.
5. The composite electrode coating with reversible protection function according to claim 1, characterized in that: The PTC effect resistance temperature of the composite electrode coating is 60°C to 120°C.
6. The composite electrode coating with reversible protection function according to claim 1, characterized in that: The lift-to-drag ratio of the PTC effect of the composite electrode coating is greater than or equal to 3.
7. Use of the composite electrode coating with reversible protection function as claimed in any one of claims 1 to 6 in a composite electrode of a lithium ion battery.
8. A lithium ion battery composite electrode, characterized in that: The invention comprises a composite electrode coating with a reversible protection function as claimed in any one of claims 1 to 6, a current collector and an active material layer.
9. A lithium ion battery composite electrode according to claim 8, characterized in that: The thickness of the composite electrode coating accounts for 0.1% to 20% of the total thickness of the composite electrode.
10. The method for preparing a lithium ion battery composite electrode according to claim 8, characterized in that: The steps include: S1: blending the conductive agent and the polymer matrix by a solution method or a melt method to obtain a polymer matrix / conductive agent composite; S2: uniformly coating the polymer matrix / conductive agent composite on the current collector by solution coating or hot pressing, and obtaining the current collector-coating composite after drying; S3: coating a layer of active material slurry on the current collector-coating composite, and obtaining a lithium-ion battery composite electrode after drying.
Citation Information
Patent Citations
Preparation method of safety coating for positive current collector in lithium ion battery
CN103956499A
Electrode and preparation method therefor
CN107437622A
Battery pole piece, preparation method of battery pole piece, and battery
CN107768597A
Method for manufacturing PTC layer
JP2018113151A
Manufacturing method of PTC polymer sheet-electrode assembly
KR1020070001041A